The Effect of Gender Diversity and Board of Directors Size on Tax Avoidance in the Banking Sector in Indonesia - Putri, Ainin Syukuria; Quinn, Princess Alicia Kerenhappuch (SERUNAI, 2025)
This study aims to analyze the effect of gender diversity and board of size on tax avoidance practices in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The issue of tax avoidance is a significant concern in corporate governance because, although legal, this practice can create ethical dilemmas and impact a company's reputation. This study used a quantitative approach with explanatory methods and purposive sampling techniques. Secondary data were obtained from the companies' annual financial reports. The dependent variable was tax avoidance, as measured by the Effective Tax Rate (ETR), while the independent variables included board size and gender diversity, as represented by the proportion of female directors. Data analysis was conducted using the Robust Regression (RLM) method. The results showed that board size had a significant negative effect on ETR, meaning that the larger the board size, the higher the level of tax avoidance. Meanwhile, gender diversity has a negative but insignificant effect on ETR, indicating that the presence of women on boards is not strong enough to suppress tax avoidance practices. This finding confirms that effective corporate governance depends on an efficient and balanced board structure. Overly large boards can reduce effective oversight, while gender diversity needs to be accompanied by empowerment and a stronger strategic role. This research provides empirical contributions to the fields of accounting and corporate governance and can inform future policy development.